The Coins of India : The Mughal Emperors. Part VIII (M8): The Coins in the Name of Jahangir Shah Including the Pre-Accession Coinage of Azim-ush Shan - Ansari, Mohammed Tariq (Brill | Manohar Publishers & Distributors, 2017)
This is the second book in our series of publications on the Coins of India. Like the earlier volume this work also presents a generational change in the method of recording, illustrating and presenting numismatic data on the coins. In the first book only the silver coins of Shah Alam I Bahadur were included but in this volume on Jahandar Shah, his coins in all three metals - gold, silver and copper have been included. Pre-accession coinage of Azimush-Shan, who lost out the battle for succession to Jahandar Shah is also included in the book. The legends on the coins and couplets have been illustrated in full colour coding. The separate sections of the coin inscriptions are clearly defined and colour coded by illustrating the individual coins - both obverse and reverse. This makes learning and understanding the calligraphic inscriptions on the coins very simple. Short histories of all the emperors and other coin issuers have been included. In this work more mint maps have been provided than in the previous volume. Changes in types and styles of the coins have been recorded carefully. The knowledge of the secrets held in these inscriptions, i.e. dates, mint, ruler's name, etc., is unlocked for all and is very easy to follow. The volume will be of immense help to coin collectors, dealers, researchers, scholars, students of numismatics and South Asian History.